Prevalence of sleep problems in Japanese preschoolers in a medium‐sized city: Community‐based survey using the Children's Sleep Habits Questionnaire. Issue 6 (19th June 2017) - Takahashi, Michio; Adachi, Masaki; Yasuda, Sayura; Osato‐Kaneda, Ayako; Saito, Manabu; Kuribayashi, Michito; Nakamura, Kazuhiko
Abstract: Although the mean score of the Children's Sleep Habits Questionnaire (CSHQ) differs between countries, there are no normative data for the CSHQ of Japanese preschoolers based on a community sample. The aims of this study were therefore to present normative data for the CSHQ and determine the prevalence and characteristics of sleep problems in Japanese preschoolers. Parents or the primary caregiver of 482 preschoolers aged 4–5 years completed the CSHQ and the Strength and Difficulties Questionnaire. Approximately 80% of preschoolers scored above the cut‐off for sleep disturbance on the CSHQ. In addition, co‐sleeping was prevalent in Japanese preschoolers but the habit of co‐sleeping contributed little to behavioral and emotional problems. Sleep problems appear to be prevalent in Japanese preschoolers based on the CSHQ, and could be associated with the Japanese sleep habit of co‐sleeping.